Tumors of the central nervous system, volume 10 pineal, pituitary, and spinal tumors - Hayat, M.A. (Tumors of the central nervous system,, 2013)
Adding to a vitally important cycle of publications covering the latest research developments in our understanding of neoplasms affecting the human central nervous system, this edition focuses on numerous aspects of pineal, pituitary, and spinal tumors. As with the previous volumes in the series, this latest work addresses a central imperative in cancer research—the need to standardize classifications, written definitions and investigative guidelines in order to achieve a measure of shared objectivity among academics engaged in one of the most important medical endeavors of our era. It brings together the very latest work by oncologists, neurosurgeons, physicians, research scientists, and pathologists, providing the medical community with a wealth of data and results that, taken together, will advance the cause of cancer research.   The volume synthesizes work on diagnosis, drug development, and therapeutic approaches that are typically scattered in a variety of journals and books. It features promising recent work in applying molecular genetics to clinical practice and evidence-based therapy, covering molecular profiling of tumors as well as a number of surgical treatments such as resection and radiosurgery. Together with its counterpart publications, it represents a much-needed central resource that will inform and guide future research efforts. Index.